Pomegranate supplementation attenuates inflammation, joint dysfunction via inhibition of NF‐κB signaling pathway in experimental models of rheumatoid arthritis. Issue 8 (17th June 2019) - Karwasra, Ritu; Singh, Surender; Sharma, Deeksha; Sharma, Shivkant; Sharma, Nitin; Khanna, Kushagra
Abstract: Incisive search of innovative compounds for regulating pain, inflammation, and bone damage, with nominal side effects has focused on nutritional supplements. The endeavor of this research work was to investigate, for first time, the inhibitory effect of pomegranate rind extract in established models of nociception and inflammation. Pomegranate (50, 100, and 200 mg/kg) and indomethacin (3 mg/kg) was assessed in eddy's hot plate‐induced algesia, carrageenan, and Complete Freund's adjuvant‐induced models in Wistar rats. Results of study conclude that pomegranate at a dose of 200 mg/kg showed significant ( p < 0.001) reduction in paw swelling in both inflammatory experimental models. In addition, observations recorded a significant ( p < 0.05) increase in nociceptive threshold. Henceforth, we might say that pomegranate (200 mg/kg) decline pain and inflammation by downregulating the activation of TNF‐R1, TNF‐α, IL‐1β, IL‐6, NF‐κB, oxidative stress markers, and tissue histology. Practical applications: The research work represents the first report on inhibitory mechanism of NF‐κB by pomegranate rind extract, enriched in tannins and flavanoids. The findings of the study provide satisfactory evidence of pomegranate rind in amelioration of adjuvant‐induced arthritis. Pomegranate rind, being enrich in bioactive compounds like phenolics and flavanoids possess potent antioxidant activity that might contribute in attenuating rheumatoid arthritis. Abstract : Pomegranate improves the associated symptoms (pain and inflammation) of rheumatoid arthritis. Implicated mechanism underlying pathogenesis of rheumatoid arthritis is explored. Pomegranate‐based product can be used for the treatment and management of chronic inflammatory disorders.